OS MODELOS DE DESEJO E DE SER HUMANO NO DISCURSO DE EDIR MACEDO - ALVES, ELTON EGYDIO (2014)
This study analyzes the models of desire and human being proposed in the speech of Bishop Macedo from theoretical Mircea Eliade and René Girard. Mircea Eliade understands the desire to live intensely religious man in the sacred sphere, this because in primitive societies the sacred drove the group life. What gods performed earlier in the founding myth should be copied by the group. With this, the parties, the calendar, the holy places, should always relate to the act of the gods, in other words, do the same that the gods did. To copy what divinity did at the beginning, the religious man was inserted into the sphere of the sacred and life received meaning. Girard, mimetic desire is the great supporter of imitation that generates what he calls mimetic mechanism. Girard, mimetic desire is the great supporter of imitation that generates what he calls mimetic mechanism. The mimetic mechanism is directly related to learning, since rituals are re-enacted the founding myth and repeated, enabling the emergence of religion and culture. Bishop Macedo emphasizes in his books and sermons some biblical figures from the Old Testament and the Christ of faith to validate his speech of prosperity and achievement, while the prophets of the Old Testament and the Jesus presented in the Gospels are poorly addressed by not representing the logical Theology of Prosperity. Relevant to the proposed topic references were used for this research, in addition to books and sermons of Bishop Edir Macedo.